2020
DOI: 10.1007/s00234-020-02481-1
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and practical aspects of semi- and fully automatic segmentation methods for resected brain areas

Abstract: Purpose Precise segmentation of brain lesions is essential for neurological research. Specifically, resection volume estimates can aid in the assessment of residual postoperative tissue, e.g. following surgery for glioma. Furthermore, behavioral lesion-symptom mapping in epilepsy relies on accurate delineation of surgical lesions. We sought to determine whether semi- and fully automatic segmentation methods can be applied to resected brain areas and which approach provides the most accurate and cost-efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 56 publications
4
20
0
Order By: Relevance
“…This measure characterizes the segmentation border reliability. Several variants of the Hausdorff distance are reported in the literature ( Bakas et al, 2018 , Gau et al, 2020 ); we report the 95 % Hausdorff distance, which is more robust to outliers. Additionally, the relationship between manual and automated resection volumes was plotted for each subject and we report the Pearson’s correlation coefficient and mean absolute error (MAE) between these variables.…”
Section: Methodsmentioning
confidence: 48%
See 2 more Smart Citations
“…This measure characterizes the segmentation border reliability. Several variants of the Hausdorff distance are reported in the literature ( Bakas et al, 2018 , Gau et al, 2020 ); we report the 95 % Hausdorff distance, which is more robust to outliers. Additionally, the relationship between manual and automated resection volumes was plotted for each subject and we report the Pearson’s correlation coefficient and mean absolute error (MAE) between these variables.…”
Section: Methodsmentioning
confidence: 48%
“…Previous studies have found a relationship between lesion size and classifier accuracy as measured by DSC and percent volume difference (PVD) between predicted and manual segmentations ( Gau et al, 2020 ). To understand whether lesion size contributed to classifier accuracy or PVD error, we partitioned subjects into small (N = 17) and large (N = 28) resection groups using the same threshold (17.92 ml) previously reported ( Tan and EfficientNet, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have focused on segmenting brain lesions, 10 , 16 to the best of our knowledge, not as many have specifically targeted brain lacunas. Gau and colleagues 11 claim to be the first group to have done so. They compared a fully automatic and a semi‐automatic approach against the manual segmentation masks and found a median DSC of 0.58 and 0.78, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We randomly selected 60 individuals with temporal lobe epilepsy (TLE) who met inclusion criteria, which is approximately two times the number used in a similar study. 11 After reviewing the quality of MR images, we excluded 4 cases due to MRI artifacts and 2 cases due to MRI signs of gliosis secondary to postoperative infection. In order to avoid the interference of blood and edema in the segmentation, we excluded patients whose postoperative MRI was performed less than five months after surgery (n = 3).…”
Section: Methodsmentioning
confidence: 99%